2009
DOI: 10.1038/jidsymp.2009.14
|View full text |Cite
|
Sign up to set email alerts
|

Non-Sunscreen Photoprotection: Antioxidants Add Value to a Sunscreen

Abstract: The association between ultraviolet radiation (UVR) exposure and both skin cancer and photo-aging is well documented. In addition to the conventional organic-chemical and physical-mineral type sunscreens, other non-sunscreen protective strategies have been developed. These include topically applied botanical extracts and other antioxidants as well as topical DNA repair enzymes. Standard terms of photoprotection such as sun protection factor (SPF) do not accurately reflect the photoprotection benefits of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 23 publications
(23 reference statements)
2
78
0
8
Order By: Relevance
“…[168] On the other hand, the natural skin care products are safe, quickly absorbed by the skin and are hypoallergenic in nature. [169] Plant extracts are considered safe, [170] because of the simple fact that they come from nature. [171] In addition, the natural herbs have despicable mammalian toxicity and can be handled safely.…”
Section: Discussionmentioning
confidence: 99%
“…[168] On the other hand, the natural skin care products are safe, quickly absorbed by the skin and are hypoallergenic in nature. [169] Plant extracts are considered safe, [170] because of the simple fact that they come from nature. [171] In addition, the natural herbs have despicable mammalian toxicity and can be handled safely.…”
Section: Discussionmentioning
confidence: 99%
“…O uso de antioxidantes, como flavonoides, por exemplo, compostos comumente encontrados em vegetais com a função de protegê-los contra radiação UV, poderia apresentar papel sinérgico e complementar os filtros solares, atuando na proteção solar (8,(14)(15)(16)(17). Alguns estudos já demonstraram evidências favoráveis com relação ao uso de óleos e extratos vegetais em formulações voltadas à proteção solar (8,17,18).…”
Section: Murumuru (Astrocaryum Murumuru)unclassified
“…Na tentativa de encontrar ingredientes alternativos e com ação fotoprotetora para aplicação em cosméticos, ocorreu sensível aumento nos estudos envolvendo compostos de origem natural. A estratégia de investigação de novos compostos envolve potencial ação antioxidante e/ou presença de cromóforos em sua molécula que them against UV radiation, could provide synergistic and complementary role in sunscreens for improved sun protection (8,(14)(15)(16)(17). Some studies have shown favourable evidence regarding the use of oils and plant extracts in formulations aimed at sun protection (8,17,18).…”
Section: Introductionunclassified
“…Antioxidants are commonly added in commercial sunscreen preparationsin order to reduce the photo-oxidative damage that results from UV-induced ROS production, providing a sort of non-sunscreen photo-protection and supplement the photoprotective effects of sunscreens [8]. These include several well characterized vitamins including vitamins C, E and β-carotene [9].…”
Section: Antioxidantsmentioning
confidence: 99%